STUDENT'S MULTIMODATED COMPETENCY IN DIGITAL LEARNING IN UNIVERSITIES - Mochamad Bayu Firmansyah; S Suwadi (Erudio Journal of Educational Innovation, 2021)
Multimodal competence of students needs to be trained as the necessary skills for the needs of technology and communication in the digital era. Technology and information skills in question are competencies to obtain information and produce knowledge in the digital era. In learning in higher education, it is expected that students can find their identity and develop naturally with lecturers' facilitators in paying attention to concepts and their psychological development. The general purpose of this study is to explain the multimodal learning model of students in higher education. Specifically includes learning steps, role guidelines, evaluation instruments and learning impacts. This research uses a qualitative approach with a case study method. Qualitative research with the case study method was chosen to gain a thorough and in-depth understanding of the multimodal learning model of students in higher education. This approach is used to explain and explore the use of student multimodal learning models in universities. The research data are students' verbal and written speech related to learning steps, role guidelines, evaluation instruments and the impact of digital learning. The results showed that the use of a learning management system (digital) in learning psychology of multimodal literature in this study could improve students' multimodal competence. Increasing students' multimodal competence is shown by interaction during the learning process. With a learning model that includes learning steps, role guidelines, evaluation instruments and learning impacts emphasizing the use of LMS and various digital learning resources, it can improve students' multimodal competence by utilizing various modal modalities (language, music, sound, images, movement).